Identifikasi Isolat Ekstrak Etanol Kulit Batang Rhizophora apiculata Blume dan Rhizophora mucronata Lam Serta Sitotoksisitasnya Terhadap Sel MCF-7 dan T47D - Joko Kristianto; Haryoto Haryoto; Peni Indrayudha (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Mangrove plants as traditional medicine have long been used by the society for the therapy of anticancer diseases. So far, the potency of mangrove plants as anticancer has not been studied intensively. The methanol extract of R. mucronata stem bark has cytotoxic activity on myeloma cells. This study aims to determine the isolates of the ethyl acetate fraction of the methanol extract of the stem bark of R. mucronata and R. apiculata, and to examine the potency of cytotoxic activity against MCF-7 and T47D cells. The powder of the stem bark of R. mucronata and R. apiculata were extracted with methanol by maceration, and then the methanol extract was fractionated consecutively using n-hexane, ethyl acetate, and methanol. Ethyl acetate fraction was then purified by column chromatography with a diameter of 2 cm and a height of 30 cm with a static phase in the form of silica gel 60 (0.063-0.2 mm) Merck 7734 and eluent n-hexane:ethyl acetate (6: 4, 5: 5, 6: 4, 7: 3, 8: 2, 9: 1) and n-hexane: methanol (9,5: 0,5) 10 ml each. The eluates that produce the same number and pattern of stains were combined into one isolate. Then the eluate was evaporated at room temperature. Then the purification results of the extract R. mucronata were isolated using preparative TLC with 0.25 mm GF254 silica gel as static phase and n-hexane mobile phase: ethyl acetate (6: 4), while the apiculata extract with n-hexane mobile phase: ethyl acetate (5: 5). The results of the stain separation of the compound were scraped off and separated from the static phase using a solvent. The purity of isolates compound was examined using TLC in the static phase of silica gel GF254 0.25 mm. The qualitative test results of the ethyl acetate fraction of R. apiculata stem bark with an NMR spectrophotometer showed a composition of cis-3- (3,5-dihydroxyphenyl) acrylic acid, while the ethyl acetate fraction of R. mucronata stem bark contained n-hexan-3-ol compounds. The cytotoxicity test of ethanol extract, n-hexane fraction, ethyl acetate fraction and ethanol extract was carried out on MCF-7 and T47D cells using the MTT method. The results proved that the ethanol extract, n-hexane fraction, ethyl acetate fraction and ethanol fraction from the ethanol extract of R. mucronata and R. apiculata stem bark, based on cytotoxic activity, were inactive against MCF-7 and T47D cells.